Transfer of learning between favirote and non-favirote hand in flooting serve in volleyball - Ghidar, Baidaa (Journal of Physical Education, 2011)
The importance of the study lies in focusing on the favorite arm in learning underhand serving in volleyball without using transfer of learning although there are many methods that stresses the use of transfer of learning to strengthen the limbs to perform with both arms. This fact led the researcher to use the favorite arm and transferring learning to the non-favorite arm. The problem of the research lies in teachers of physical education not focusing on non-favorite arm which if trained can help strengthen the favorite arm. The aims of research: 1. Identifying the effect of learning and transfer of learning from the favorite arm to the non favorite arm in underhand serving in volleyball. 2. Identifying the best learning due to transfer of among the three groups in underhand serving. The researcher used the experimental method. The subjects were 15 first – year students from the college of physical education / university of Baghdad. They were divided into three groups; the first group used the favorite arm, the second group used non favorite arm and the third group used both favorite and non favorite arms. The researcher came up with the following conclusions: 1. There is positive effect on both favorite and non favorite arms in learning underhand serving in volleyball. 2. There are variances among the three experimental groups. The third experimental group showed a development in learning underhand serving in volleyball. Finally the researcher came up with the following recommendations: 1. Benefiting from transfer of learning between the limbs due to its importance in acquisition. 2. Stressing the importance of playing with both limbs to develop the non favorite limb with the favorite one and vice versa. 3. Making similar studies on other limbs in other sports